Dampak Perubahan Curah Hujan Terhadap Tingkat Kerentanan Erosi Tanah Di Sub DAS Merawu, Jawa Tengah - Donnie Koes Nugraha; Bayu Dwi Apri Nugroho; Chandra Setyawan (The University of Lampung, 2021)
This research was held to estimate rainfall and change in soil erosion vulnerability from 2020 to 2050 in Merawu Sub-Watershed, Banjanegara District with RCP 2.6, 4.5 and 8.5. The RCP is an overview of the concentration trends for greenhouse gases, aerosols and land use change created by the climate modeling community. Rainfall prediction was generated from SDSM Software and combined with USLE to predict soil erosion in ArcGIS 10.4. Changes in rainfall intensity are an important factor in changes of soil erosion rates because the kinetic energy of falling rainwater can cause soil erosion.The results showed rainfall in Banjarnegara Station at 2020-2050 with RCP 2.6,4.5 and 8.5 were increasing by +0,26%; +0,60%; +0,52%, while in Kalisapi Station were decreasing by -1,54%; -1,65% dan -2,20%. The change of soil erosion vulnerability prediction showed that soil erosion in Sub-DAS Merawu at 2020-2050 with RCP 2.6,4.5 and 8.5 in very light category were -0,02%;-0,02%;-0,03%, light category were -0,17%;-0,17%;-0,17%, moderate category -0,05%;-0,05%;-0,04%, heavy category -0,26%;-0,35%;-0,37%, and very heavy category were +1,46%;+1,88%;+1,95%. While the average soil erosion prediction at RCP 2.6, 4.5 and 8.5 were +0,86, +1,19% and +1,03%, respectively. Keywords: soil erosion prediction, rainfall prediction, SDSM Software, Sub-DAS Merawu